Prognostic Factors for Delayed Healing of Complex Wounds in Adults: A Scoping Review Protocol - Raquel Marques; Marcos Lopes; Paulo Ramos; João Neves Amado; Paulo Alves (MDPI AG, 2022)
(1) Background: The high prevalence of persons with wounds and its consequences for a person's quality of life makes the issue a relevant focus of attention for healthcare professionals. Through prognostic factors for healing, the individual risk of complications can be predicted, is possible to predict imminent delays and guide decision-making, thus helping healthcare professionals. (2) Methods: A scoping review performed according to JBI methodology and guided by the Preferred Reporting Items for Systematic Reviews extension for Scoping Reviews (PRISMA-ScR) checklist will aim to identify the studies that meet predefined eligibility criteria. Five databases and gray literature will be the sources used to research adults with pressure ulcers, venous leg ulcers, arterial ulcers, or diabetic foot ulcers and report the prognostic factors for delayed healing in any care setting. (3) Results: This review will consider all quantitative and mixed studies in the last five years. The selection of articles will be carried out by two reviewers independently, using EndNoteWeb and Rayyan. Prognostic factors will be presented by design study, sampling, setting, outcome, wound type, and statistical methods. (4) Conclusions: Mapping prognostic factors for delayed healing could also be a starting point for a systematic review and meta-analyses to quantify the value of each factor.